A Brief Overview of AFM Force Distance Spectroscopy - Khatiwada, Devendra; Lamichhane, Shobha Kanta (Himalayan Physics, 2011)
Study of forces between the sample and the AFM cantilever tip is the basic in AFM force distance study. AFM plays vital role and acts as the Hooken’s response giving rise to the force measurement. Force characterization depends on various conditions. That yield basic theories like JKR , DMT interaction etc. have been using for its explanation. Key words: AFM; Hooken's response; UHV; JKR; DMT The Himalayan Physics Vol.2, No.2, May, 2011 Page: 80-83 Uploaded Date: 1 August, 2011